BOBABOX MARKETING COMMUNICATION STRATEGY IN BUILDING BRAND IMAGE THROUGH INSTAGRAM SOCIAL MEDIA - Pratama, Sapta Wahyu; Rasyid, Abdul (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
By putting the correct marketing plan into practice, a firm can increase consumer trust in its brand and increase that brand's loyalty. In Medan, the use of Instagram for boba drink product marketing has the potential to capture a significant portion of the market, so beverage businesses will find it easier to establish a positive brand image with careful use and promotion. The purpose of this study is to identify and characterize Bobabox's use of Instagram social media for brand image building in marketing communications. This study, which was carried out at the production head office, Bobabox Jl. Setia Budi No. 157 in Medan City, employs descriptive qualitative research methodologies. It will be put into practice in April and May of 2024. The results of this study show that @bobabox.id uses five elements of marketing communication in building brand image including, advertising by using the Instagram ads feature, sales promotion by creating promotional content and collaboration, public relations providing the best service, direct marketing presenting linktree to facilitate consumers and personal selling through endorsements